Knowledge, attitude and practices regarding smoking amongst young females - Singh, Isha; Sharma, Manjushri; Sharma, Isha; Sharma, Pooja; Garg, Kranti; ., Deepali (International Journal of Research in Medical Sciences, 2020)
Background: Smoking amongst women is increasing in the developing countries like India. There is paucity of data on the knowledge, attitude and practices of smoking amongst females in India. Hence a study was planned to assess the same. Methods: It was a qualitative research using descriptive questionnaire, prepared using the basic protocols available as per WHO Global Adult Tobacco Survey, conducted by self-reporting, from February to March, 2018 in the University Institute of Applied Management Sciences, Panjab University, Chandigarh. It was administered to 111 females aged 18 to 35 years, residing in Chandigarh. Results: Total22.5% of the female respondents were current smokers. Majority of them belonged to the age group of 26-35years; were either employed or were studying and felt that females resorted to smoking for gaining pleasure and relieving stress. Most of them were aware of passive smoking. Majority felt that people who smoke should quit for their own health and for their families and street plays, public awareness camps, television and cinema halls are important mediums for helping to quit. Will power be found to be most important to help smokers quit. Some quoted the role of nicotine replacement therapy, exercise, individual counseling etc also. Majority of the females started smoking early, at an age of 16-25years, consuming 1-10cigarettes per day and had been smoking since more than a year when interviewed. Smoking was primarily introduced by peers. All the smokers were aware of different types of smoking hazards, most commonly reported as cancer and asthma. 16/25 smokers wanted to quit and 14/16 had tried in the past but were unsuccessful. Conclusions: This study gives an indication of rising smoking trend in females. Smoking cessation measures need to be made more gender-sensitive, targeting females in their early ages.